2020
DOI: 10.1123/jsr.2018-0363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Foot Exercises on Foot Posture, Pain, Disability, and Plantar Pressure in Pes Planus

Abstract: Context: Pes planus is a prevalent chronic condition that causes foot pain, disability, and impaired plantar load distribution. Short-foot exercises are often recommended to strengthen intrinsic foot muscles and to prevent excessive decrease of medial longitudinal arch height. Objective: To investigate the effects of short-foot exercises on navicular drop, foot posture, pain, disability, and plantar pressures in pes planus. Design: Quasi-experimental study. Setting: Biomechanics laboratory. Participants: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 21 publications
4
53
0
7
Order By: Relevance
“…Following this argument, Moon et al checked whether performing the SFE produced a tendency toward a more normalized posture of the foot [ 3 ]. This was similar to the work of Unver et al who stated that enhancing the IFM with the SFE (for six weeks) tended to normalize the foot’s posture in flat feet with respect to the ND and the FPI [ 32 ]. These conclusions were similar to those obtained in other studies with shorter training periods (SFE for three minutes a day for four weeks) [ 9 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Following this argument, Moon et al checked whether performing the SFE produced a tendency toward a more normalized posture of the foot [ 3 ]. This was similar to the work of Unver et al who stated that enhancing the IFM with the SFE (for six weeks) tended to normalize the foot’s posture in flat feet with respect to the ND and the FPI [ 32 ]. These conclusions were similar to those obtained in other studies with shorter training periods (SFE for three minutes a day for four weeks) [ 9 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…As noted, there is no unified protocol that presents scientific evidence about how to train with the SFE (variations in the period of implementation of four to eight weeks, training daily, or three days per week [1,3,4,[10][11][12]26,32]. Mignogna et al, after conducting a critical study in relation to three articles based on the SFE in healthy subjects, presented the limitations of the results obtained, which reached a scientific evidence level of 2.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished proprioception in CAI arises in part from reduced mechanoreceptor sensory afferent inputs and/or weakened postural reflex responses, which is mediated by the spinal cord [ 29 ]. SFE itself enables augmentation of sensory input by increasing plantar pressures [ 36 ]. HD-tDCS, on the other hand, selectively modulates the excitability of the cerebral cortex and may thus have limited effects on the spinal components of the proprioceptive system.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a positive correlation between calcaneal inclination angle and foot arch height 31 , an increase in the foot arch height may become the important target of regular training for enhancing sprint performance in sprinters. This is because the foot arch height can be increased by short foot exercise training 36 38 . Mulligan and Cook 37 reported that the short foot exercise training increased the foot arch height when weight bearing in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%